Anxiety among fathers during the prenatal and postpartum period: a meta-analysis - Jenn A. Leiferman; Charlotte V. Farewell; Jennifer Jewell; Rachael Lacy; Jessica Walls; Benjamin Harnke; James F. Paulson (Taylor & Francis Group, 2021)
Introduction The purpose of this review was to determine the prevalence of anxiety among fathers during the perinatal (pre- and post-natal) period. Methods A systematic search was conducted to identify studies published between 1995-2020. One hundred and seventy-two of the records met inclusion criteria and full texts were screened for eligibility. The authors followed PRISMA guidelines to extract the data. Results A total of 23 studies, representing 40,124 participants, are included in this meta-analysis. The overall random effects estimate of paternal perinatal anxiety was 10.69% (95% confidence interval (CI): 8.14 − 13.91%). Rates of paternal perinatal anxiety demonstrated significant heterogeneity that was large in magnitude (Q = 304,494, p < .001, I2 = 99.93 and τ2 = .5381). Study quality rating did not appear to moderate rates of paternal perinatal anxiety (low: 10.74%; 95% CI: 6.56-17.11%; high: 10.65%; 95% CI: 6.02- 18.15%). Discussion Paternal perinatal anxiety rates in this meta-analysis are considerably higher than the global WHO regional prevalence rates for anxiety among men suggesting the transition into parenthood may place men at greater risk for anxiety.